1997
DOI: 10.1103/physrevb.56.r8526
|View full text |Cite
|
Sign up to set email alerts
|

Electric and magnetic properties and phase diagram of a series of organic superconductorsλBETS2GaXz

Abstract: The physical properties of a series of organic superconductors with fourfold quasistacking structures, -BETS 2 GaX z Y 4Ϫz ͓BETSϭbis͑ethylenedithiotetraselenafulvalene; X,Y ϭF, Cl, Br; 0ϽzϽ2)] are changed continuously by tuning the value of z. The compound -BETS 2 GaBr z Cl 4Ϫz , has a superconducting ground state for 0ϽzϽz c ͑Ϸ0.8͒ and a semiconducting state for z c ϽzϽ2.0. The maximum T c is about 10 K, showing the existence of a 10-K class of non-ET organic superconductors ͓ETϭbis͑ethylenedithio͒tetrathiafu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 14 publications
3
32
0
Order By: Relevance
“…As reported in -type BETS conductors, the decrease of unit cell volume induced by the BrPCl exchange in MX anions produces &&chemical pressure'' in the crystal lattice (20,21). Similar to the real pressure, the chemical pressure enhances the metallic nature of the system.…”
Section: Small T Of -(Be¹s) Feclmentioning
confidence: 89%
“…As reported in -type BETS conductors, the decrease of unit cell volume induced by the BrPCl exchange in MX anions produces &&chemical pressure'' in the crystal lattice (20,21). Similar to the real pressure, the chemical pressure enhances the metallic nature of the system.…”
Section: Small T Of -(Be¹s) Feclmentioning
confidence: 89%
“…The structural parameters are refined by the standard Rietveld technique [18] and the fitting between the experimental spectra and the calculated values is relatively good based on the consideration of lower RP values as shown in Table 1. The electronic bandwidth W has been used to discuss magnetic and transport properties of perovskites with varied A-site doping [15,19]. The empirical formula of the bandwidth W for ABO 3 -type perovskites using the tight binding approximation [20] is W ∝ cos ω/(d Mn-O ) 3 Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…At zero magnetic field, -(BETS) 2 FeCl 4 shows the metal-insulator transition at ϳ8 K, which is associated with the antiferromagnetic order of the Fe ions. [1][2][3][4][5][6][7][8] In contrast, the isostructural -͑BETS͒ 2 GaCl 4 remains metallic and has a superconducting transition at ϳ6 K. 5 The insulating phase for -(BETS) 2 FeCl 4 is destabilized by the magnetic field above ϳ10 T, 3,4,7 where the paramagnetic state of the Fe moments is induced by the fields. In the insulating phase, a spin-flip transition from the uniaxial antiferromagnetic ͑AF͒ state to the canted antiferromagnetic ͑CAF͒ state is present around 1 T. 3,4,7 Quite recently, it was reported that superconductivity is induced above 17 T below 1 K when the magnetic field is applied exactly parallel to the conduction plane ͑ac plane͒.…”
Section: Introductionmentioning
confidence: 97%